Orbital and Premaxillary Emphysema as a Result of Nose-Blowing Following Blepharoplasty - Bilge Tarım; Meltem Kılıç (Indian Journal of Plastic Surgery)
A 41-year-old man presented with sudden-onset swelling, redness, and pain in the right eye, 4 days after bilateral upper and lower eyelid blepharoplasty. The symptoms were preceded by a forceful nose-blowing episode. Upon examination, periorbital edema and subcutaneous crepitus were observed, along with limitations in upward gaze. Computed tomography revealed bilateral premaxillary and extraconal air accumulation. Since there was no optic nerve ischemia or orbital compartment syndrome, the patient was closely monitored. Spontaneous regression of the emphysema was observed during follow-ups. Orbital emphysema, although commonly associated with trauma, can also arise from compelling movements such as severe nose-blowing, as demonstrated in this unique case postblepharoplasty. The structural changes during surgery may contribute to weakened support, predisposing patients to emphysema following sudden pressure changes. Clinicians should be vigilant for periorbital edema and subcutaneous crepitus after facial surgeries, emphasizing the importance of timely imaging for diagnosis. Awareness campaigns advising against forceful actions like sneezing, coughing, and nose-blowing during the initial postoperative period are crucial to prevent potential complications.